External Quality Monitoring of the Cervical Cytopathological Exams in the Rio de Janeiro City - Vânia Stiepanowez de Oliveira Rocha; Solange da Silva Malfacini; Alex Moreira Gomes; Cláudia Ramos Marques da Rocha (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To discuss the implementation and contributions of the External Quality Monitoring in the city of Rio de Janeiro and to analyze the performance of the main providers of cervical cytopathology in this city from September 2013 to March 2017, here referred to as "Alpha laboratory" and "Beta laboratory." Methods Observational, cross-sectional, retrospective study using information from the Cervical Cancer Control Information System (SISCOLO, in the Portuguese acronym), municipal coordinationmodule, External QualityMonitoring report. The proportions of false positives, false negatives, unsatisfactory samples and rejected samples were estimated. The agreement among the observers was analyzed through the Kappa index and the reduction of disagreements in the period for each laboratory studied, comparing the results of each cycle. Results A total of 19,158 examinations were selected, of which 19,130 (99.85%) were monitored, 16.649 (87, 03%) were reviewed by the External Quality Monitoring Unit, 2,481 (12,97%) were rejected and 441 (2,65%) were considered unsatisfactory. The "Beta laboratory" presented excellent concordance in all cycles; the "Alpha laboratory" had good concordance in the first two cycles (K = 0.76 and 0.79), becoming excellent in the following four cycles. The average Kappa index was 0.85, with median of 0.86. The percentage of diagnostic disagreement was 6.63% of the reviewed exams, of which 5.38% required a change of conduct Conclusion External Quality Monitoring is an exercise in diagnostic improvement, and its implementation was fundamental to ensure the reliability of the cytopathological exams in the city of Rio de Janeiro.